Integrating Madura’s Salt Potential into Science Learning Through Pop-Up Book for 4th Grade of Ponteh 1 Elementary School - Conny Dian Sumadi; Ach. Kusairi S (PAEDAGOGIA, 2025)
Integrating natural potential into learning can support programs to achieve learning completion and increase environmental awareness. Integrated science learning must be supported by several things such as Pop-Up Book. The research aimed to (1) analysis of the integration of Madura salt potential into Natural Resources and Conservation material for grade 4 elementary school in the form of Pop-Up books (2) analysis of student learning activities using Pop-Up books Madura’s Salt Potential. The research was conducted by analysing learning materials to be able to integrate the Madura’s salt potential through pop-up book. Data instruments used for observed the learning activities was observation sheets in learning activities. The research using the material carried out in 4 times at school. From the research obtained related to the competency analysis carried out to integrate Madura Salt Potential through Pop-Up Books on the material of Natural Resources and Their Conservation. The results obtained were that the material of Natural Resources and Their Conservation can be integrated with Madura salt potential. Learning activities by integrating Madura Salt Potential through Pop-Up Books increased from the 1st day, which was 92% for the 2nd day to the 4th day, which was 96%. This shows that students can integrate Madura Salt potential through Pop-Up Books